Neumonía enzoótica porcina en la provincia de Mendoza: un estudio descriptivo - Blois, A. (2017)
The objective of the study was to determine Mycoplasma hyopneumoniae infection and the presence of swine enzootic pneumonia (SEP) in pigs of herds from Mendoza province. In each of five herds, 18 to 20-week-old pigs were observed looking for non-productive cough and 20 of these pigs were sampled for PCR (nasal swab). The pigs were slaughtered at abattoir, where their lungs were inspected looking for SEP-compatible macroscopic lesions. Prevalence of lung lesions, percentage of affected area, and pneumonia index were calculated. In addition, 20 lung samples were collected for histopathology and bronchoalveolar lavage (BAL) for PCR. The presence of the agent in BAL samples (20% - 90%) was observed in all herds, as well as a high percentage of macroscopic (57% - 97%) and microscopic (10% - 40%) lung SEP-compatible lesions and non-productive cough (6% - 25%). The results obtained in the present study would indicate that more than half of 50-500 sow herds in Mendoza province are infected with M. hyopneumoniae and that the impact of the NEP is important in these herds.